EFEKTIVITAS KEBIJAKAN MONETER TERHADAP PERTUMBUHAN EKONOMI - Ningsih, Liasulistia; Arisna, Puput; Hatmawan, Aglis Andhita; Tanjung, Indra Ismayudi; Suhendra, Noval; Hartini, Hartini (STAI Darul Qalam Tangerang, 2024)
The success of economic performance is inseparable from the role of the policies implemented by the government. The uncertain economic cycle has forced the government and monetary authorities to implement various policy programs to stabilize the macro economy so that the economy can grow sustainably. The purpose of this research is to look at the effectiveness of monetary policy as one of the policy programs to stabilize the economy in the Sumatra region. The data used in this study is secondary data in the period 2010-2021 using a panel data analysis tool. The results of the analysis show that monetary policy has a significant effect on economic growth in the Sumatra region. The policies implemented are in accordance with the theory, in which monetary policy is implemented in the opposite direction to the economic cycle. Meanwhile, inflation and poverty also have a negative and significant effect on economic growth